STUDI PENGARUH KONSENTRASI HCl DAN WAKTU AGING (PEMATANGAN GEL) TERHADAP SINTESIS SILIKA XEROGEL BERBAHAN DASAR PASIR KUARSA BANGKA - Meirawati, Dian; Wardhani, Sri; Tjahjanto, Rachmat Triandi (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Synthesis and characterization of silica-based xerogel Bangka quartz sand has been done through the sol-gel method. Synthesis is done with the first is the manufacture of sodium silicate precursor and then the addition of HCl to pH 1 and the addition of 1M NaOH to pH 7 for sol formation, Aging then performed gel (gel aging) as a polymerization reaction completion. HCl concentration and aging time are used respectively - were 0.5, 1 and 2 M then 12, 18 and 24 hours. Gel that had formed was washed with distilled water and printed in the syringe then dried in an oven for 18 hours at a temperature of 80 0C. Based on the test results the surface area of ​​the methylene blue is the optimum condition in 0.5 M HCl and aging time of 12 hours. The surface area of ​​the silica xerogel is  9.060 m2g-1. Characterization by FTIR showed wide uptake in wave numbers 3468.84 cm-1 is the OH groups of Si-OH and Si-O of Si-O-Si in the wave number 1080.06 cm-1. XRD results produce is amorphous silica xerogel.   Keywords: Sol-gel, Sodium silicate, xerogel.